Rekonstruksi Gigi dalam Odontologi Forensik: Tinjauan Naratif - Natalia Tjingson; Maria Rini Wulan Dhari; Siti Salsabila Kirana (Universitas Udayana, 2025)
Background: In the event where identification isn’t achievable using DNA or fingerprint methods, teeth could act as primary identifier considering its unique anatomy. Through the comparative identification method, teeth can be utilized as a personal identifier, allowing differentiation of individuals based on their unique dental characteristics. Furthermore, the human dentition has an undeniably strong durability due to its composition, enabling it to withstand various extreme conditions. Nevertheless, there is still a possibility that teeth will shatter into fragments, or even completely destroyed when subjected to high temperatures. In such situations, forensic odontology plays a crucial role in reconstructing teeth from fragments or remaining sockets for identification purposes. Purpose: This study aims to review the implementation of tooth reconstruction for personal identification purposes in forensic odontology. Methods: A comprehensive review of literature related to tooth reconstruction in forensic odontology was conducted through 3 electronic databases, which arePubMed, Google Scholar, and ScienceDirect. Results: Based on the literature review, tooth reconstruction is performed through both conventional and digital methods. Conventionally, dental impression and restorative material (commonly composite resin) were utilized. On the other hand, digital reconstruction requires a scanner and CAD/CAM program. Both methods share the same concept in rebuilding a replica that conforms to the natural anatomy of the original tooth. Conclusion: Tooth reconstruction aids in identification by rebuilding its anatomy using remaining fragments or sockets. Tooth reconstruction can be performed utilizing both traditional and digital methods. This study is expected to spread awareness of tooth reconstruction as a potential tool in the field of forensics, especially for the identification process.